(untitled) (Medico Legal Update, 2019)
Most transgenders in India reside in secluded or in outskirts of society with very low status; they are often addressed in a very derogatory manner by the society. The Indian sub-continent displays a variety of studies undertaken by the cheiloscopic experts and most researchers could differentiate the two genders due to their characteristic lip pattern. Many of them carried out double blind study inorder to identify the gender on the basis of lip-patterns identified by them. But the “third gender” was left out and never taken into consideration. Present cheiloscopic study throws light on various lip-patterns present in them and whether they have characteristic patterns. The paper also reviews the relevance of various studies undertaken in Indian Subcontinent, social problems existing in transgenders and further explains cheiloscopic relevance in forensics